1998
DOI: 10.1016/s0304-4238(97)00144-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of nutrients and water in rockwool slabs

Abstract: During the 1980s, soilless cultures expanded enormously. Since then several kinds of substrates, both biodegradable and non biodegradable, have been developed. In this research the physicochemical characteristics of one of the most commonly used chemical inert substrates "rockwool" is investigated. The flow patterns occurring in rockwool slabs under both laboratory and practical situations were investigated, using a pigmented nutrient solution. As the 2 rockwool slabs became more saturated, flow patterns were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 3 publications
0
40
0
1
Order By: Relevance
“…The nutrient control should vary depending upon the climate of greenhouses and development stage of plants (De Rijck and Schrevens, 1998). Such integrated control systems combining climate and nutrient, however, have not become wide spread in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient control should vary depending upon the climate of greenhouses and development stage of plants (De Rijck and Schrevens, 1998). Such integrated control systems combining climate and nutrient, however, have not become wide spread in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of soil-limited factors (expensive chemical soil disinfection methods, low yields and possible plant residues, water shortage and increase in salinity of natural soils) has increased demand for a suitable technology adapted to soilless culture (De Rijck and Schrevens 1998) and exploitation of local materials for use as growing media with specific physicochemical properties (Ortega et al 1996). Inorganic substrates such as perlite, sand and pumice, are chemically inert, making it possible to supply nutrients in a controlled manner (De Rijck and Schrevens 1998). Several studies reported the favorable effect that organic materials have on plant growth (Sawan and Eissa 1996, Tehranifar et al 2007, Tzortzakis and Economakis 2008, as increased substrate porosity and water holding capacity (Hardgrave and Harriman 1995).…”
mentioning
confidence: 99%
“…Leachate EC was the highest after each flushing event in RWF (data not shown), although the average leachate EC during the experiment was the same for RWL and RWF (Table 1). This can be explained by the tendency of water in drip irrigation to flow downwards rather than to spread horizontally (De Rijck & Schrevens, 1998). In this way, salt accumulated around the wet bulb produced by the dripper and the flushing washed out some of these salts.…”
Section: Resultsmentioning
confidence: 99%